A Book, a Securitate File, and a Research Project. On Gossiping and Ethnography - Thériault, Barbara (Eurostudia, 2015)
Katherine Verdery’s latest book, an ethnography of the Archive of Romania’s Secret Police and the permission to copy and study a Securitate file, that of Iuliana, represents, for the author, the opportunity to write an unusual book review. Superposing the book and the file allows her to reflect on the work of secret police officers and that of ethnographers as well as questioning the practice of the sociological observer. As it turns out, the file adds a new dimension and an interpretation key to the book: beyond the importance of networks or social relationships as material secret police officers and ethnographers share, it discloses gossip as an empirical source and a recruitment technique. Centering on gossip helps the author in reformulating one of the book’s central arguments and delineating the contours of the “bourgeois,” a figure at the core of a new research project. The extreme character of the two cases at hand—material constituted toward a political end—sheds light on the relations ethnographers entertain to their informants as well as to dilemmas of research, which might otherwise remain unseen.